Low-carbon preparation of blast furnace burden from iron ore concentrates via cold-bonding process: New insights into the effect of concentrate type - Xiaolong Wang; Zhiyun Ji; Xiaohui Fan; Min Gan; Shaochun Li; Shengxuan Fan; Zengqing Sun; Jiaming Lv; Yanqing Du; Jiasheng Li; Ying Yu (Minerals Engineering, 2026)

Time-resolved volatile profiles and molecular-species lipid remodeling during lipase treatment of anhydrous milk fat - Anqi Chen; Qingyun Xu; Jiaming Li; Yanxi Chen; Qiance Shen; Guocheng Du; Jianghua Li; Jian Chen (Food Research International, 2026)

Cyclic biomineralization by incorporating iron-oxidizing and sulfate-reducing microorganisms for sustainable iron removal and sulfur recovery from acid mine drainage: Efficiency and mechanism - Xingjie Wang; Ling Liu; Yuxuan Yang; Jiaming Du; Liyuan Ma; Jie Tang; Peng Liu; Jianwei Zhou (Minerals Engineering, 2026)

Nanoconfined humic acid-supported nZVI enhances imidacloprid remediation without compromising soil microbiome or exacerbating ARG health risks - Na Li; Jiaming Yi; Lin Zhu; Du Chen; Meizhen Wang; Dan Huang (Environmental Research, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Maternal Stress During Pregnancy Induces Higher Anxiety-Like Behavior in Male Mice Offspring Under Acute Stress by Upregulating CRF/CRFR1 and Driving Time-Specific Activation of the MHb-IPN Circuit - Yujie Wang; Jiajia Zhao; Yueyang Wang; Zhixin Du; Li Wang; Zibo Ma; Siyang Sun; Xinyang Qu; Xiaohan Geng; Jiaming Yan; Liping Yang; Junlin Hou (Neuroscience Bulletin, 2026)

A novel approach to distinguish the respective contributions of galvanic effect and reactive oxygen species on sulfide mineral dissolution: Insights from stibnite and pyrite - Xiaoqian Li; Jingxuan Qiu; Xingjie Wang; Jiaming Du; Deng Liu; Chun Li; Hongmei Wang; Liyuan Ma (Chemical Geology, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Development of an indirect ELISA and an immunochromatographic test method for early detection of Haemonchus contortus infection in sheep - Xueqiu Chen; Lingyun Mou; Manqin Deng; Jingju Zhang; Jiaming Yu; Jianfang Li; Hongli Zhang; Guangxu Ma; Yi Yang; Aifang Du (Veterinary Parasitology, 2026)

An Investigation of PSO-Optimized LSTM–Transformer Hybrid Model for Multi-Step Ship Motion Prediction - Yilu Peng; Qing Hai; Jiaming Zhang; Lingwei He; Yongyu Huang; Lin Du; Yiming Qiang (Journal of Marine Science and Engineering, 2025)
The advantages of hybrid models for time series forecasting have received significant attention, and several studies focus on and test their application in the seakeeping of ship motions. A hybrid model integrating an LSTM encoder and Transformer decoder (LT) is introduced to overcome the limitation of individual LSTM and Transformer: initially, the seakeeping response of the KCS ship was simulated by ANSYS-AQWA considering the sea state 3 and 4 simultaneously and established a dataset; secondly, three standalone baseline models (LSTM, Transformer, and TCN), and two hybrid models, LT and LT, with PSO-optimized hyperparameters (P-LT) were constructed and trained to forecast the seakeeping performance of ships with multiple steps of 30, 60 and 90; finally, the comparison between solo and hybrid models was made by different steps on RMSE, MAE and NRMSE evaluations to prove the advancement of LT and P-LT models. The P-LT hybrid model achieved consistent accuracy improvements compared with the best-performing individual models across different ship motions. Notably, RMSE reductions were observed at all prediction horizons (30, 60, and 90 steps), with maximum improvements reaching 13.54% for rolling, 11.83% for pitching, and 12.87% for heaving motions. This study provides both theoretical and practical support to ship motion prediction and demonstrates the potential of the proposed study as an effective engineering product for enhancing safety in ship operation.

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Advancing kombucha fermentation: Microbial interactions, functional metabolites, and innovative optimization strategies - Anqi Chen; Jiaming Li; Aiping Yao; Guocheng Du; Jianghua Li; Jian Chen (Food Chemistry, 2025)

Research on the dynamic properties of rubber-recycled brick-coarse aggregate concrete through pore structure evolution - Shucheng Yuan; Jiayu Zeng; Jiaming Mai; Siwei Du; Yanjindong Yi; Kunpeng Li; Wei Liang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Dual redox-centered p(thiophene-TPA) conjugated polymers for high-performance flexible electrochromic supercapacitors - Xu Cheng; Chunhui Du; Jiaming Li; Yuqiao Zhang; Wenyuan Xu; Jianming Zhang; Hui Shi; Ge Zhang; Long Zhang (Chemical Engineering Journal, 2025)

High performance two photon polymerization resin designed for sub-micron precision and millimeter scale structure manufacturing - Jiaming Hu; Yang Gao; Lukun Wu; Bowen Zheng; Ning Li; Kai Du; Jing Li; Shuai Zhang (Chemical Engineering Journal, 2025)

Cement-MgO synergetic stabilized earth-straw mix: From material performance to building simulation - Jiaming Cui; Junjie Li; Yi Du; Guillaume Habert (Energy and Buildings, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Hotspots of wetland loss to impervious surfaces in the conterminous United States - Zhenhua Zou; Chengquan Huang; Megan W. Lang; Ling Du; Greg McCarty; Jeffrey C. Ingebritsen; Jane Harner; Rusty Griffin; Weishu Gong; Jiaming Lu (Science of The Total Environment, 2024)

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

Kinematic Stability Analysis of Anchor Cable Structures in Submerged Floating Tunnel under Combined Parametric–Vortex Excitation - Jiaming Xiong; Song Sang; Youwei Du; Chaojie Gan; Ao Zhang; Fugang Liu (Journal of Marine Science and Engineering, 2024)
The submerged floating tunnel is a marine transportation infrastructure that links two shorelines. The tunnel tube body’s buoyancy exceeds gravity, with anchoring ensuring equilibrium. Anchoring reliability is crucial. This study presents a three-way coupled kinematic model for the mooring structure, formulated on Hamilton’s principle and Kirchhoff’s assumption. It explores the impact of the tube body’s buoyancy-to-weight ratio and the sea current’s angle of incidence on mooring motion response. By solving the motion analysis model, Hill’s equation system is derived to assess the parameter instability of the anchor cable structure. The coefficient of excitation instability intervals for the submerged floating tunnel is determined and validated. The findings indicate the following: (1) Increasing the float-weight ratio reduces displacement response amplitudes in all directions, bringing downstream and transverse currents closer to their initial positions; (2) Changes in current direction angles result in decreased downstream excitation strength and increased transverse displacement response with the same excitation direction; (3) The instability interval visualization effectively predicts anchor cable structure instability under parametric excitation. Structures within the instability region are deemed unstable, while those outside are considered stable.

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Comparative study on dynamic responses of integrated installation process of a 5-MW and a 15-MW offshore wind turbine considering a pre-installed foundation - Jiaming Liu; Zhongming Xiao; Kai Wang; Shuo Huang; Yu Du (Ocean Engineering, 2024)

Research on anode pressure control and dynamic performance of proton-exchange membrane fuel cell system for vehicular application - Heng Wei; Changqing Du; Xingyi Li; Chenxu Shi; Jiaming Zhang (Fuel, 2024)

Multiscale Feature Fusion for Hyperspectral Marine Oil Spill Image Segmentation - Guorong Chen; Jiaming Huang; Tingting Wen; Chongling Du; Yuting Lin; Yanbing Xiao (Journal of Marine Science and Engineering, 2023)
Oil spills have always been a threat to the marine ecological environment; thus, it is important to identify and divide oil spill areas on the ocean surface into segments after an oil spill accident occurs to protect the marine ecological environment. However, oil spill area segmentation using ordinary optical images is greatly interfered with by the absorption of light by the deep sea and the distribution of algal organisms on the ocean surface, and it is difficult to improve segmentation accuracy. To address the above problems, a hyperspectral ocean oil spill image segmentation model with multiscale feature fusion (MFFHOSS-Net) is proposed. Specifically, the oil spill segmentation dataset was created using hyperspectral image data from NASA for the Gulf of Mexico oil spill, small-size images after the waveband filtering of the hyperspectral images were generated and the oil spill images were annotated. The model makes full use of having different layers with different characteristics by fusing feature maps of different scales. In addition, an attention mechanism was used to effectively fuse these features to improve the oil spill region segmentation accuracy. A case study, ablation experiments and model evaluation were also carried out in this work. Compared with other models, our proposed method achieved good results according to various evaluation metrics.

Observation of black carbon in Northern China in winter of 2018–2020 and its implications for black carbon mitigation - Yang Wang; Qiuge Ju; Zhenyu Xing; Jiaming Zhao; Song Guo; Fuxing Li; Ke Du (Science of The Total Environment, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

Hollow 1D carbon tube core anchored in Co3O4@SnS2 multiple shells for constructing binder-free electrodes of flexible supercapacitors - Jiaming Wang; Ying Huang; Xianping Du; Shuai Zhang; Meng Zong (Chemical Engineering Journal, 2023)

Comparative analysis of husk microstructure, fruit quality and concentrations of bioactive compounds of different pomegranate cultivars during low temperature storage - Qianting Liu; Xiaohong Guo; Jiaming Du; Yidan Guo; Xiaocheng Guo; Liping Kou (Food Bioscience, 2023)

Spatiotemporal patterns of fire-driven forest mortality in China - Jie Zhao; Jiaming Wang; Yifan Meng; Ziqiang Du; Hui Ma; Linghua Qiu; Qi Tian; Liang Wang; Mengyang Xu; Hongfei Zhao; Chao Yue (Forest Ecology and Management, 2023)

Design, synthesis, and biological evaluation of dual-target COX-2/5-LOX inhibitors for the treatment of inflammation - Le Du; Shuaishuai Du; Jiaming Li; Hongwei Wang (Medicinal Chemistry Research, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Design, synthesis and biological evaluation of indoline derivatives as multifunctional agents for the treatment of ischemic stroke - Shuaishuai Du; Fan Jin; Jiaming Li; Xiaodong Ma; Hongwei Wang; Shihu Qian (Medicinal Chemistry Research, 2022)

Corrosion Mechanism of 5083 Aluminum Alloy in Seawater Containing Phosphate - Jiaming Wang; Haodong Yang; Min Du; Jian Hou; Wenshan Peng; Cunguo Lin (Journal of Ocean University of China, 2021)

Investigation of the SA evolution by using the CHAOS-4 model over 1997–2013 - JiaMing Ou; AiMin Du; WenYao Xu (Science China Earth Sciences, 2016)

A high resolution lithospheric magnetic field model over China - JiaMing Ou; AiMin Du; E. Thébault; WenYao Xu; XiaoBo Tian; TieLong Zhang (Science China Earth Sciences, 2013)